Determinants of personal exposure to PM2.5 and black carbon in Chinese adults: A repeated-measures study in villages using solid fuel energy. (January 2021) - Lee, Martha; Carter, Ellison; Yan, Li; Chan, Queenie; Elliott, Paul; Ezzati, Majid; Kelly, Frank; Schauer, James J.; Wu, Yangfeng; Yang, Xudong; Zhao, Liancheng; Baumgartner, Jill
Highlights: PM2.5 exposures were on average 2 times higher than outdoor PM2.5 . Men and women had similar exposures to PM2.5 after accounting for smoking. Within-individual variances were much larger than between-individual variances. Indoor sources explained 7–28% of between-individual variance in PM2.5 exposure. Outdoor PM2.5 explained 16% of within-individual variance in PM2.5 exposure. Abstract: Exposure to air pollution is a leading health risk factor. The variance components and contributions of indoor versus outdoor source determinants of personal exposure to air pollution are poorly understood, especially in settings of household solid fuel use. We conducted a panel study with up to 4 days of repeated measures of integrated gravimetric personal exposure to PM2.5 and black carbon in 787 men and women (ages 40–79) living in peri -urban villages in northern (Beijing and Shanxi) and southern (Guangxi) China. We simultaneously measured outdoor PM2.5 and collected questionnaire data on sociodemographic characteristics and indoor pollution sources including tobacco smoking and solid fuel stove use. We obtained over 2000 days of personal exposure monitoring which showed higher exposures in the heating season (geometric mean (GM): 108 versus 65 μg/m 3 in the non-heating season for PM2.5 ) and among northern participants (GM: 90 versus 59 μg/m 3 in southern China in the non-heating season for PM2.5 ). We used mixed-effects models to estimate within- and between-participant variance components and to assess the determinants of exposures. Within-participant variance in exposure dominated the total variability (68–95%). Outdoor PM2.5 was the dominant variable for explaining within-participant variance in exposure to PM2.5 (16%). Household fuel use (PM2.5 : 8%; black carbon: 10%) and smoking status (PM2.5 : 27%; black carbon: 5%) explained the most between-participant variance. Indoor sources (solid fuel stoves, tobacco smoking) were associated with 13–30% higher exposures to air pollution and each 10 μg/m 3 increase in outdoor PM2.5 was associated with 6–8% higher exposure. Our findings indicate that repeated measurements of daily exposure are likely needed to capture longer-term exposures in settings of household solid fuel use, even within a single season, and that reducing air pollution from both outdoor and indoor sources is likely needed to achieve measurable reductions in exposures to air pollution.